The Role of Artificial Intelligence in Diagnosis and Clinical Decision-Making in Nursing - Saudi , La; Putri, Meizha Nadzwa Riyadi; Putri, Alvita Prilea; Abidin, Dorothy Aurellita; Widyadhana, Kalyca Najmi Anindya (International Conference on Biomedical and Sports Medicine, 2025)
The integration of Artificial Intelligence (AI) into healthcare is profoundly reshaping nursing diagnosis and clinical decision-making. This study explores how AIparticularly Clinical Decision Support Systems (CDSS) and Decision Support Systems (DSS)has enhanced nursing practice between 2020 and 2025. Employing a mixed-method approach combining bibliometric analysis, participatory system design, and qualitative field studies in Europe, the research identifies emerging trends, practical challenges, and implementation opportunities in AI-enabled nursing care. Bibliometric data reveal a surge in global publications focusing on early detection, diagnostic accuracy, and personalized care. Participatory studies conducted in Germany and Austria illustrate how AI tools reduce nursing workload, aid complex decisions, and improve interprofessional coordination. However, concerns remain regarding data privacy, system transparency, and the erosion of human interaction. The findings emphasize the need for AI to function as a cognitive partner, complementing rather than replacing nurses. Successful integration depends on ethical design, contextual adaptation, and human-centered development. In low-resource settings like Indonesia, AI-aligned digital interventions have significantly improved maternal health education and pediatric nutrition. This study concludes that AI holds transformative potential when developed collaboratively, applied ethically, and tailored to diverse healthcare contexts. Future research should investigate long-term impacts, equity in access, and nursing competencies for safe and empathetic AI use.